Validação do 2000 Bernstein-Parsonnet e EuroSCORE no Instituto do Coração - USP Validation of the 2000 Bernstein-Parsonnet and EuroSCORE at the Heart Institute - USP - Omar Asdrúbal Vilca Mejía (Brazilian Journal of Cardiovascular Surgery, 2012)
OBJETIVO: Validar o 2000 Bernstein Parsonnet (2000BP) e EuroSCORE aditivo (ES) na predição de mortalidade cirúrgica nos pacientes operados de coronária e/ou valva, no Instituto do Coração da Universidade de São Paulo (InCor/ HC-FMUSP). MÉTODOS: Desenho prospectivo e observacional. Foram analisados, 3000 pacientes consecutivos operados de coronária e/ou valva, entre maio de 2007 e julho de 2009 no InCor/HC-FMUSP. A mortalidade foi calculada com os escores 2000BP e ES. A correlação entre mortalidade estimada e mortalidade observada foi validada mediante testes de calibração e discriminação. RESULTADOS: Houve diferença significativa na prevalência dos fatores de risco entre as populações do estudo, ES e 2000BP. Os pacientes foram estratificados em cinco grupos para o 2000BP e três para o ES. Na validação dos modelos, o ES apresentou uma boa calibração (P=0,596); no entanto, o 2000BP revelou-se inadequado (P=0,047). Na discriminação, a área abaixo da curva ROC revelou-se boa para ambos os modelos, ES (0,79) e 2000BP (0,80). CONCLUSÃO: Na validação, o 2000BP revelou-se questionável e o ES adequado para predizer mortalidade nos pacientes operados de coronária e/ou valva, no InCor/ HC-FMUSP. OBJECTIVE: To validate the 2000 Bernstein Parsonnet (2000BP) and additive EuroSCORE (ES) to predict mortality in patients who underwent coronary bypass surgery and/or heart valve surgery at the Heart Institute, University of São Paulo (InCor/HC-FMUSP). METHODS: A prospective observational design. We analyzed 3000 consecutive patients who underwent coronary bypass surgery and/or heart valve surgery, between May 2007 and July 2009 at the InCor/HC-FMUSP. Mortality was calculated with the 2000BP and ES models. The correlation between estimated mortality and observed mortality was validated by calibration and discrimination tests. RESULTS: There were significant differences in the prevalence of risk factors between the study population, 2000BP and ES. Patients were stratified into five groups for 2000BP and three for the ES. In the validation of models, the ES showed good calibration (P = 0.596), however, the 2000BP (P = 0.047) proved inadequate. In discrimination, the area under the ROC curve proved to be good for models, ES (0.79) and 2000BP (0.80). CONCLUSION: In the validation, 2000BP proved questionable and ES appropriate to predict mortality in patients who underwent coronary bypass surgery and/or heart valve surgery at the InCor/HC-FMUSP.